Association study between genome‐wide significant variants of vitamin B12 metabolism and gastric cancer in a han Chinese population. Issue 4 (9th March 2016) - Zhao, Lei; Wei, Yucai; Song, Ailing; Li, Yumin
Abstract: Gastric cancer is one of the leading causes of cancer mortality worldwide. Accumulating evidence suggests that vitamin B12 plays an important role in the development of gastric cancer. Genome‐wide association studies on metabolites in the one‐carbon metabolism pathway identified several vitamin B12‐related polymorphisms. Therefore, we investigated the association between variants within vitamin B12‐related genes and gastric cancer in a Han Chinese population. Eight variants within the genome were significant vitamin B12‐related genes, and they were selected for analysis in this case–control study. This study used a total of 492 gastric cancer patients and 550 noncancer controls. The variant rs526934 from the TCN1 gene was associated with an increased risk of developing gastric cancer. Increased risks of gastric cancer occurrence were observed in the minor G allele (OR = 1.25, 95% CI = 1.03–1.52, P = 0.031) and GG genotype (OR = 2.06, 95% CI = 1.24–3.42, P = 0.0043) compared with the wild‐type A allele and AA‐GA genotype, respectively. In the haplotypic analysis, we found that the CUBN haplotypes were associated with an altered gastric cancer risk. The rs1801222T/rs11254363A (OR = 1.40, 95% CI = 1.05–1.86, P = 0.021) and rs1801222C/rs11254363G (OR = 4.39, 95% CI = 2.32–8.30, P < 0.0001) haplotypes exhibited an increased gastric cancer risk, while rs1801222T/rs11254363G showed protective effects against gastric cancer (OR = 0.43, 95% CI = 0.25–0.73, P = 0.002) compared with the wild‐type rs1801222C/rs11254363A haplotype. The circulating vitamin B12 concentration‐related variants were associated with the occurrence of gastric cancer. This finding shed light on the unexpected role of vitamin B12 metabolism genes in gastric carcinogenesis and highlighted the interplay of diet, genetics, and human cancers. © 2016 IUBMB Life, 68(4):303–310, 2016